Predicting Colonoscopy Time: A Quality Improvement Initiative - Deepanshu Jain; Abhinav Goyal; Stacey Zavala (Clinical Endoscopy, 2016)
Background/Aims There is lack of consensus on the optimal time allotted for colonoscopy, which increases patient wait times. Our aim was to identify and quantify the individual pre-procedural factors that determine the total procedure time (TPT) of colonoscopy. Methods This retrospective study involved 4,494 subjects, undergoing outpatient colonoscopy. Effects of age, sex, body mass index, abdominal surgery history, procedure indication (screening, surveillance, or diagnostic), procedure session (morning or afternoon), and endoscopist’s experience (fellow or attending) on TPT were evaluated using multiple regression analysis. A p<0.05 was considered significant. Results A total of 1,239 subjects satisfied the inclusion/exclusion criteria. Women, older individuals, and those with a history of abdominal surgery were found to have a shorter TPT (p>0.05) as did afternoon session colonoscopies (p=0.004). Less experienced endoscopists had longer TPTs (p>0.05). Screening (p=0.01) and surveillance (p=0.008) colonoscopies had a longer TPT than diagnostic procedures. Overall, the F-value of the regression model was 0.0009. Conclusions The indication for colonoscopy and the time of day have statistically significant associations with TPT. These results will help in streamlining workflow, reduce wait time, and improve patient satisfaction.